2006
DOI: 10.1161/01.str.0000222915.55103.78
|View full text |Cite
|
Sign up to set email alerts
|

Response to Letter by Larsen et al

Abstract: Response to Letter by Larsen et al Response:It is correct that the stated protective effect of Eprosartan over Nitrendipine concerns the composite primary end points. As pointed out in the statistical section of the article, we summed up the number of primary end points and the observation time in each group to be able to calculate an event rate per group. However, because of limited space in the article, we could not state in detail that before we computed any statistical test, we ascertained that event frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 2 publications
0
11
0
1
Order By: Relevance
“…One trial, Paramedic Initiated Lisinopril For Acute Stroke Treatment (PIL-FAST; 64% were ischemic stroke patients), was further excluded because a results in patients with ischemic stroke were not reported separately from those with intracranial hemorrhage or stroke-mimicking conditions (Figure 1). 13 Our final analysis included 13 RCTs, [8][9][10][11][14][15][16][17][18][19][20][21] comprising 12 703 individuals, with 6392 (50%) participants randomly assigned to the active treatment group and 6311 (50%) to the control group. The study design, quality, and baseline characteristics of these RCTs are shown in Tables 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One trial, Paramedic Initiated Lisinopril For Acute Stroke Treatment (PIL-FAST; 64% were ischemic stroke patients), was further excluded because a results in patients with ischemic stroke were not reported separately from those with intracranial hemorrhage or stroke-mimicking conditions (Figure 1). 13 Our final analysis included 13 RCTs, [8][9][10][11][14][15][16][17][18][19][20][21] comprising 12 703 individuals, with 6392 (50%) participants randomly assigned to the active treatment group and 6311 (50%) to the control group. The study design, quality, and baseline characteristics of these RCTs are shown in Tables 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
“…Most trials were conducted in Europe, whereas 1 large trial was from China. Analyzed data were abstracted from whole trials that enrolled only patients with ischemic stroke (6 trials), 10,[14][15][16][17]19 separately reported subgroups of patients with ischemic stroke (6 trials), 9,11,18,[20][21][22] and a separately reported subgroup of patients with ischemic stroke enrolled within 72 hours (1 trial). 8 The median time from stroke onset to randomization ranged from 11 to 58 hours.…”
Section: Resultsmentioning
confidence: 99%
“…24,25 Recently, a few preliminary randomized trials of blood pressure reduction in acute ischemic stroke have been published. [26][27][28][29] A phase 2 pilot trial of therapy with the angiotensin receptor blocker candesartan cilexetil was stopped early because of significantly lower mortality and fewer vascular events at 12 months in the treatment group, although blood pressure was similar between the 2 study groups. 26 However, a larger phase 3 trial (SCAST [Scandinavian Candesartan Acute Stroke Trial]) of candesartan therapy enrolling 2029 patients with acute stroke (ischemic or hemorrhagic) showed that the composite vascular end point did not differ between the treatment groups at 6 months, despite a significant difference in blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…6,8,9 The study was also based on findings from experimental studies and 1 clinical study indicating that candesartan has beneficial effects in the acute phase of stroke. 10 The absence of any sign of beneficial effects in SCAST might imply that treatment was started too late to limit brain injury, and that blood pressure reduction after the first few hours can only reduce cerebral perfusion and increase brain injury even Data are n (%), mean±SD, or median (interquartile range). ACE indicates angiotensin-converting enzyme; DBP, diastolic blood pressure; mRS, modified Rankin Scale; OCSP, Oxfordshire Community Stroke Project; SBP, systolic blood pressure; SSS, Scandinavian Stroke Scale; and TIA, transient ischemic attack.…”
Section: Discussionmentioning
confidence: 99%